Unpacking social innovation by nonstate service providers in the challenging social work practice (Journal of Comparative Social Work, 2022)
Nonstate service providers in the form of nongovernmental organizations (NGOs) play an important role in the delivery of social services and the development of social work practice, in particular in fragile and conflict-affected countries. In such challenging settings, NGOs also mobilize various resources, implement novel activities or service delivery models that may induce the development of social innovation; however, such perspectives have been overlooked in the social work literature. This study outlines a framework for understanding how social innovation generates by nonstate service providers in a challenging social work context. By analyzing 15 interviews from Bosnia and Herzegovina, the study identified three interrelated key mechanisms that drive social innovation by local NGO service providers: a) transcopy, b) coactive novelty and c) knowledge construction. The processes underlying these mechanisms include transnational networking, copying and adapting, contextual modification, relationship-building, pioneering novel solutions, knowledge production and transfer. This study offers new insights into the role of nonstate service providers in the development of social innovation in a challenging social work context and has several implications for practice.